Konstruksi Citra PT Kereta Api Indonesia (Persero) Melalui Perubahan Logo Perusahaan - Alfath Riadhul Fauzi; Ari Pandu Witantra; Atih Ardiansyah (Jurnal Inovasi dan Kreativitas (JIKa), 2022)
Problems: PT Kereta Api Indonesia (Persero) needs to construct their corporate image in accordance with changes in the company's vision and mission, new transformation, changes in corporate culture, and the strategic theme Technology Enhanced. Against this background, KAI has rebranded the Logo which needs to represent the Company's new values which creates a new image for PT KAI (Persero). Purpose: The purpose of this study is to find out how PT KAI (Persero) can shape the corporate image according to the new changes through the Rebranding Logo. Methodology: This research uses the Constructivism paradigm with a descriptive qualitative approach and a case study research method. Data collection methods used were interviews, participant observation, and documentation studies. The research informants were selected using the snowball sampling technique and the research was conducted at the Head Office of PT Kereta Api Indonesia (Persero) Jl. Pioneers of Independence 1, Bandung City, West Java. Results/Findings: The results of this study indicate that by changing its logo, KAI wants to image the company as no longer just a railroad service. They want to portray KAI as the best transportation ecosystem provider in Indonesia. They also want to transform into a new company through rebranding. They also incorporate the new cultural values "AKHLAK" into their new Logo and represent the Technology Enhanced theme to develop the Company's services and operations using the use of technology and digitalization. Paper Type: Case Study